Analysis of humoral immune responses to recombinant Chlamydia pneumoniae antigens. (February 2020) - Hagemann, Jürgen Benjamin; Simnacher, Ulrike; Marschall, Miriam Theresia; Maile, Julia; Soutschek, Erwin; Wellinghausen, Nele; Essig, Andreas
Highlights: Novel data on humoral immune responses to a panel of Chlamydia pneumoniae antigens are provided. Virulence-associated TARP is an early sensitive (80.0%) antigen for IgM detection. Hypothetical protein YwbM is a sensitive (up to 94.4%) and specific (95.1%) IgG marker. Abstract: Objectives: Chlamydia pneumoniae is a difficult to diagnose respiratory pathogen. This study was performed to systematically characterize humoral immune responses to selected C. pneumoniae antigens in order to provide novel serodiagnostic perspectives for clinical and epidemiological issues. Methods: Based on a literature search, gene library screening, and serological proteome analysis, 15 immunogenic surface-associated, virulence-associated, and hypothetical C. pneumoniae antigens were selected, recombinantly expressed, and lined on a nitrocellulose strip. Specific IgM and IgG reactivity was measured in a total of 172 PCR- and micro-immunofluorescence testing (MIF)-characterized serum samples from patients with respiratory infections. A theoretical model was conceived to approximate a putative course of C. pneumoniae antigen expression and assess the potential of early and late antigens. Results: While surface antigens performed poorly, the virulence-associated TARP was a reliable antigen for IgM detection, with a sensitivity of 80.0% and a diagnostic specificity of 90.2%. The hypothetical protein YwbM proved powerful for IgG detection with MIF-correlative sensitivities of up to 94.4% and a diagnostic specificity of 95.1%. Conclusions: This study provides new insights into antibody profiles to immunogenic proteins in C. pneumoniae infection. The study findings offer antigen candidates for more reliable and standardized serological investigations of C. pneumoniae infections, including studies on seroprevalence and epidemiology.